Dissolution of semicrystalline polymer fibers: Numerical modeling and parametric analysis. Issue 4 (6th February 2017) - Ghasemi, Mohammad; Singapati, Abhiram Y.; Tsianou, Marina; Alexandridis, Paschalis
Abstract : The solvent processing of polymers is significantly constrained by polymer chain crystallinity. A phenomenological model is developed here that captures the phenomena governing the dissolution of semicrystalline polymers, for example, solvent penetration, transformation from crystalline to amorphous domains, specimen swelling, and polymer chain untangling. The model is validated for the case of cellulose fiber swelling and dissolution in an ionic liquid. A parametric sensitivity analysis is performed to assess the impact of decrystallization rate constant, disentanglement rate, concentration dependence of solvent diffusivity, disentanglement threshold, and thickness of external boundary layer on the swelling and dissolution of semicrystalline polymer fibers. The rate of dissolution after attaining maximum swelling is found to be mainly controlled by the polymer chain disentanglement rate. The insights obtained from this study would facilitate the design of efficient solvent systems and processing conditions for the dissolution of semicrystalline polymers such as cellulose, polyglycolic acid, and polyesters. © 2017 American Institute of Chemical Engineers AIChE J, 63: 1368–1383, 2017